IMPLEMENTASI KTSP DALAM PEMBELAJARAN BAHASA DAN SASTRA INDONESIA DI SMP - Ahmad Zuhri; Karomani Karomani; Edi Suyanto (Universitas Lampung, 2014)
The research is aimed at describing teachers’ comprehension ability towards KTSP and its implementation in Indonesian language and literature learning. It used a descriptive method with primary and secondary data. The source of the data was Indonesian language and literature teachers at SMPN 2 Tegineneng. The data collecting technique was triangulation through questionnaires and observation sheets. The data analysis technique was descriptive quantitative. The research findings are: 1) the comprehension towards KTSP was categorized high; 2) based on the class observations, the preparation and implementation stages were categorized good; 3) the KTSP document was categorized ‘enough’ which means it could be used as a reference for Teaching and Learning Activities in Academic Year 2012/2013.Penelitian bertujuan mendeskripsikan pemahaman terhadap KTSP dan implementasi dalam pembelajaran Bahasa dan sastra Indonesia. Metode penelitian yang digunakan adalah deskriptif dengan data primer dan sekunder. Sumber data penelitian ini adalah guru Bahasa dan Sastra Indonesia SMPN 2 Tegineneng. Teknik pengumpulan data adalah teknik triangulasi menggunakan instrumen angket dan lembar observasi. Teknik analisis data deskriptif kuantitatif. Hasil penelitian (1) pemahaman terhadap KTSP berkategori tinggi. (2) berdasarkan observasi kelas, tahap persiapan dan pelaksanaan berkategori baik, (3) Dokumen KTSP berkategori cukup, artinya dapat dijadikan acuan dalam pelaksanaan KBM tahun pelajaran 2012/2013.Kata kunci: guru, implementasi, ktsp 2006.